2022
DOI: 10.4274/jtgga.galenos.2021.2021-0004
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy, acceptability and continuation of postpartum, post-abortive progestin-only pill: a pioneering prospective multicentric study from Turkey

Abstract: Objective: The aim of this study was to evaluate the efficacy, side-effects and continuation rate of the desogestrel-progestin-only-pill (POP) in postpartum and post-abortive Turkish women and its relation with breast-feeding. Material and Methods: In this prospective multicentric study women who delivered (or had surgical abortion) and wanted to receive POP for contraception were recruited to the study. The follow-up visits were scheduled at the third, sixth and ninth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Also, in a study by Dutta et al [ 28 ], no differences were found in the amount of milk produced, growth, and the development of infants between the DSG ( n = 200) and PLACEBO ( n = 200) groups for 6 months, starting at 6 weeks postpartum [ 28 ]. Dilbaz et al [ 29 ] also reported no negative effects of DSG on breastfeeding among 4964 women (DSG from day 21 postpartum). During follow-up, the percentage of women breastfeeding at 3, 6, and 9 months postpartum was 68.4%, 54.8%, and 58.5%, respectively [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, in a study by Dutta et al [ 28 ], no differences were found in the amount of milk produced, growth, and the development of infants between the DSG ( n = 200) and PLACEBO ( n = 200) groups for 6 months, starting at 6 weeks postpartum [ 28 ]. Dilbaz et al [ 29 ] also reported no negative effects of DSG on breastfeeding among 4964 women (DSG from day 21 postpartum). During follow-up, the percentage of women breastfeeding at 3, 6, and 9 months postpartum was 68.4%, 54.8%, and 58.5%, respectively [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dilbaz et al [ 29 ] also reported no negative effects of DSG on breastfeeding among 4964 women (DSG from day 21 postpartum). During follow-up, the percentage of women breastfeeding at 3, 6, and 9 months postpartum was 68.4%, 54.8%, and 58.5%, respectively [ 29 ]. On the other hand, in a study by Janus et al [ 30 ], after 28 days of DSG use (3 months postpartum), contraception was discontinued due to the onset of scrotal hair in the newborn (resolved at 11 months) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 However, the incidence of unwanted and distressing forms of abnormal uterine bleeding (AUB) was sign-ificantly higher with POCs than with other methods. [2][3][4][5][6][7] There is a need for a better understanding of the mechanisms of AUB in women using POCs, 8 and thus for individualized treatment rather than the current empirical lines of therapy. 9 Office hysteroscopy (OH) has long been used to examine the uterine cavity in many gynecological conditions such as AUB, 10 unexplained infertility, and recurrent pregnancy loss.…”
Section: Introductionmentioning
confidence: 99%